The Report of the President's Committee on the NRA - Mason, Edward S. (Quarterly Journal of Economics, 1937)
Journal Article The Report of the President's Committee on the NRA Get access Edward S. Mason Edward S. Mason Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 51, Issue 3, May 1937, Pages 545–550, https://doi.org/10.2307/1884842 Published: 01 May 1937